Systematic differences of retail exchange rate spreads in some EU countries: the banks against financial integration. Valuutade jaekursside kursivahede süstemaatilised erinevused mõnedes Euroopa Liidu riikides: pangad versus finantsintegratsioon - Listra, Enn; Rahu, Katrin; Vaiser, Niina (Estonian Discussions on Economic Policy, 2012)
An important policy goal in European Union has been integration of markets and economic convergence. The aim of this exploratory paper is to study pricing of currency exchange services based on bid-ask spreads in commercial banks and the policy implications of the delayed integration of banking markets. The currency rate spreads in different bank groups and countries are compared with each other. The main results of the study are that statistically significant differences exist in the spreads set by banking groups in different countries. All banking groups in the sample offer more favorable rates in Western countries indicating that the pricing policy of bank groups may be discriminatory. Further research is needed to understand the extent and the mechanism of it and to determine which policy measures may help to overcome the problem.